Novel 2,6-diformyl-4-methyl phenol based chemosensor for Zn-II ion by ratiometric displacement of Cd-II ion and its application for cell imaging on human melanoma cancer cells - Mitra, Debarshan; Venkatathari, N.; Sabharwal, S. C.; Godbole, S. V.; Tyagi, A. K.; Das, Sangbrita (Journal of the Indian Chemical Society, 2015)
A new chelating ligand [4-methyl-2,6-bis-(pyridin-2-yl-hydrazonomethyl)-phenol] (1) was prepared by the condensation of 2-hydrazinylpyridine with 2,6-diformyl-p-cresol. Compound 1 exhibits weak fluorescence due to intramolecular photoinduced electron transfer (PET). The sensor (1) demonstrates Zn2+-specific emission enhancement due to ``PET off'' process through a 1 : 1 binding mode with the metal ion. The fluorescence quantum yield of the chemosensor 1 is only 0.020, and it increases more than 14-fold (0.280) in the presence of one equivalent of the zinc ion. Interestingly, the introduction of other metal ions causes the fluorescence intensity to remain either unchanged or weakened except for Cd2+. Ratiometric displacement of Cd2+ ion from the complex by Zn2+ ion supports the formation of more stable sensor-Zn2+ complex over the sensor-Cd2+ complex. The experimental findings have been correlated with theoretical results using B3LYP functional and 6-31G(d,p), LANL2DZ basis set for Cd2+ (2) and Zn2+ (3) complex, respectively, by Density Functional Theory (DFT) method. Moreover, the ability of probe 1 to sense Zn2+ within human melanoma cancer cells has been explored, and the Zn2+-probing process in living cells was reversible. [Mn-2(PHMP)(2)](ClO4)(2) (4) and [Ni-2(PHMP)(H2O)(5)](NO3)(3) (5) have been also synthesized and characterized crystallographically and spectroscopically to understand the ligating behavior of the ligand PHMP.
Keywords: Cd-II ion; Chemosensor; Density functional theory; human melanoma cancer cells; photoinduced electron transfer; Zn-II ion